Causal attributions of impulsive and compulsive behaviors - Astudillo-Reyes, Karla; Sánchez, Ana I.; Luna-Adame, María; Martínez, María Pilar; Muñoz-López, Lucas (Frontiers in Psychiatry, 2024)
Introduction: Aggression, and therefore gender-based violence, can be an impulsive or compulsive behavior, depending on the consumption of alcohol and/or drugs. In Europe, the prevalence of gender-based violence is 16 to 23%. This prevalence shows that there is a need to make further progress in the treatment of aggression against women. Qualitative techniques allow us to understand perceptions and attributions holistically by analyzing what people who commit the crime say, why they say it and how they say it. Aim: To explore the experience of physical and verbal aggression by a partner, dependent on the presence or absence of alcohol and drug use, in the prison population. Method: A mixed methodology was used (combining qualitative and quantitative techniques). The sample was made up of 140 men divided into two focus groups [with alcohol and/or drug consumption (SAD) and without alcohol and/or drug consumption (NSAD)] who completed the Demographic, Criminal and Behavioral Interview in Penitentiary Institutions; the Gender Violence Questionnaire (both developed for this study) and the MultiCAGE CAD-4 Questionnaire. Qualitative data were analyzed using thematic analysis and quantitative data were obtained using contingency tables. Results: it was found that the SAD group attributed the crime committed to alcohol and/or drug consumption, while the NSAD group attributed it to jealousy and to their partner. The SAD group revealed that the consequence of the physical aggressions was to get what they were looking for from their partner and the consequences of the verbal aggressions was regret, unlike the NSAD group that did not get anything from the aggressions. The SAD group recognized that to avoid future aggressions they would have to avoid alcohol and/or drug use, while the NSAD group mentioned that they would have to avoid contact with their partner. Discussion: The need to include perceptions and attributions as well as the use of alcohol and/or drugs is emphasized when assessing individuals who commit the crime of gender-based violence.